Sexed Sentiments : Interdisciplinary Perspectives on Gender and Emotion. - Ruberg, Willemijn (Critical Studies., 2010)
Sexed Sentiments provides a gender perspective on the recent turn to affect in criticism. It presents new work by scholars from different disciplines working on gender and emotion, a field par excellence where an interdisciplinary focus is fruitful. This collection presents essays from disciplines like history, literary studies, psychology, sociology and queer studies, focusing on subjects varying from masculinity in the cult of sensibility to the role of empathy in forging feminist solidarities. The volume illuminates how new theoretical approaches to both gender and emotion may be productive.